PENGALIHAN INVESTASI TABUNGAN DEPOSITO MENJADI PRODUK ASURANSI YANG DIKAITKAN DENGAN INVESTASI (PAYDI): The (Conversion/Transformation) of Deposit Savings Investment into Investment-Linked Insurance Products (PAYDI) - Dafi, Alleina Syarifa; Setyaningsih (Faculty of Law, Universitas Trisakti, 2025)
The banking industry plays a crucial role in the economy.Banks or banking institutions have the function of collecting and channeling public funds, and one of the banking activities regulated by Law Number 10 of 1998 on Banking is the collection of funds from the public in the form of time deposits and deposit certificates. On the other hand, in this modern era, an insurance institution not only acts as a protection or coverage provider for insured objects, but also serves as a means for investment. Insurance companies now offer many Investment-Linked Insurance Products (PAYDI), commonly known as 'unit-linked' products, which combine life insurance and investment services simultaneously. The concept of PAYDI allows for collaboration between banks and insurance companies, integrating two distinct activities into a cooperative relationship known as bancassurance. PAYDI offers attractive profit potentials for policyholders, but on the other hand, it may encounter obstacles in its implementation if PAYDI is made with the involvement of bank(bancassurance) and through the redirection outside the business model that has been regulated in the regulations of the legislation, such as assets linked through the transfer of investments like Deposits involving PT Asuransi Jiwasraya with a customer of a bank that has a cooperative relationship with PT Asuransi Jiwasraya. This study is a normative study with descriptive characteristics to be further analyzed qualitatively to find out whether the transfer of investment forms of deposits to PAYDI is permitted along with the provisions governing it, then drawn the deductive conclusion that such transfer is not specifically regulated in the regulations of the legislation and becomes possible only on the basis of agreement of the parties.